(untitled) (Romano-arabica, 2025)
This paper aims to present the version of an unedited poem of ʿAbd ar-Raḥmān al-Būṣīrī preserved in the Conti Rossini Archive at the Accademia Nazionale dei Lincei in Rome. The poem was composed on the occasion of the occupation of Libya by the Italian Army in 1911 and its themes are war, occupation, resistance and ḥamāsah (lit. “valour”). The poem, which constitutes an important expression of Libyan Amāzīġ heritage, has no title and was most likely copied by Conti Rossini himself. The poem is written in classical Arabic and is composed of nineteen lines, each of which is divided into two hemistichs. The present work will focus on the linguistic and literary aspects of the poem and the description of its salient features, function and meaning. The literary text, such as the one presented in this article, represents a textual typology characterized by a high quality of both linguistic and cultural input. It allows us to appreciate the art of the poet and his contribution to the literary tradition, to understand the characteristics of the historical period taken into consideration and, more generally, the culture of a population. In addition, literary text, especially that written in classical Arabic, is a valuable tool for teaching the Arabic language itself; indeed, it is an authentic and real text, which leads the student to a personal re-elaboration of the contents and, consequently, to a greater production in terms of linguistic output. Thus, its use should be re-evaluated in teaching Arabic language in today’s Academia.